Cognition Improvement in Taekwondo Novices Over 40. Results from the SEKWONDO Study - Pons Van Dijk, Gaby; Huijts, Marjolein; Lodder, Jan (Frontiers in Aging Neuroscience, 2013)
Abstract Age-related cognitive decline is associated with increased risk of disability, dementia and death. Recent studies suggest improvement in cognitive speed, attention and executive functioning with physical activity. However, whether such improvements are activity specific is unclear. Therefore, we aimed to study the effect of one year age-adapted Taekwondo training on several cognitive functions, including reaction/ motor time, information processing speed, and working and executive memory, in 24 healthy volunteers over forty. Reaction and motor time decreased with 41.2 seconds and 18.4 seconds (p=0.004, p=0.015), respectively. Digit symbol coding task improved with a mean of 3.7 digits (p=0.017). Digit span, letter fluency, and trail making test task-completion-time all improved, but not statistically significant. The questionnaire reported “better” reaction time in 10 and “unchanged” in 9 of the nineteen study compliers. In conclusion, our data suggest that age-adapted Taekwondo training improves various aspects of cognitive function in people over 40, which may, therefore, offer a cheap, safe and enjoyable way to mitigate age-related cognitive decline.